An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

SWAT-UQ: A platform for uncertainty analysis, calibration and optimization of SWAT models - Mengtian Wu; Meihong Wu; Ruochen Sun; Xuan Huang; Shuo Yan; Jianjun Han; Qingyun Duan (Environmental Modelling & Software, 2026)

Modeling and characterizing errors in satellite and reanalysis precipitation estimates using a two-step decomposition procedure - Zhehui Shen; Mingze Ding; Ruochen Huang; Hao Wu; Bin Yong (Journal of Hydrology, 2026)

Whole genome sequencing reveals transmission dynamics and persistence of Listeria monocytogenes along the poultry slaughtering and processing chain - Ye Wang; Chaohui Huang; Sijie Wu; Jianye Jia; Tianxiang Pan; Ruochen Wang; Jing Li; Zegang Wang; Chuang Meng; Yuelan Yin; Xin'an Jiao (International Journal of Food Microbiology, 2026)

Investigation on in-situ and ex-situ catalysis of metal salt in biomass photo-thermal pyrolysis: Effects on decoupled primary and secondary reactions - Dexin Huang; Gongxiang Song; Ruochen Li; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2026)

Study on the Effect of Elevators in the Vertical Plane on the Motion Performance of a Twin Hybrid Autonomous Underwater Vehicle by Simulation - Jiafeng Huang; Kele Zhou; Hyeung-Sik Choi; Ruochen Zhang; Phan Huy Nam Anh; Dong-Wook Jung; Mai The Vu (Journal of Marine Science and Engineering, 2025)
The Twin Hybrid Autonomous Underwater Vehicle (THAUV) is an underwater monitoring system consisting of a twin buoyant body and a fixed wing mounted between them. It is equipped with two propeller thrusters and a pair of elevators at the aft end. As a new type of underwater vehicle, it combines the long endurance of an underwater glider (UG), the high-speed maneuverability of an autonomous underwater vehicle (AUV), and the ability to carry larger payloads. In this paper, the motion equations of the THAUV are established, and its simulation model is developed using SIMULINK. Computational fluid dynamics (CFD) is further employed to identify hydrodynamic parameters under different elevator size conditions. A case study is conducted to analyze the effects of three different widths of elevators on glide performance, including gliding speed, pitching angle, and gliding trajectory. CFD results show that when the elevator deflection angle is zero, the hydrodynamic forces acting on the THAUV increase as the elevator width increases under identical angle of attack and velocity conditions. Under CFD conditions with fixed angle of attack and flow velocity, the sensitivity of the hydrodynamic characteristics to elevator deflection became significantly more pronounced. Increasing the elevator deflection angle led to substantial growth in the generated hydrodynamic forces. Motion simulations further show that increasing the elevator deflection angle enhances the THAUV’s gliding performance. Comparative results also reveal that glide performance improves with larger elevator width.

A comprehensive review and future research directions of ensemble learning models for predicting building energy consumption - Zeyu Wang; Yuelan Hong; Luying Huang; Miaocui Zheng; Hongping Yuan; Ruochen Zeng (Energy and Buildings, 2025)

Bottom-up nucleation induced conformal crystallization for inverted MA-free perovskite solar cells on textured substrates - Ruochen Liu; Jiawei Xu; Tianxiang Hu; Xiang Li; Kongxiang Wang; Qi Huang; Zhongtao Duan; Hong Liu; Weifan Qian; Haiting Zhou; Chunxiao Cong; Xiaofei Yue; et al. (Chemical Engineering Journal, 2025)

Composite edible film mimicking cell wall based on arabinoxylan, β-glucan and nanocellulose: Microstructural, physico-chemical properties, and preservation effect - Yingting Li; Ruifeng Ying; Ruochen Wu; Meigui Huang (Food Bioscience, 2024)

Self-assembled multifunctional Prussian blue analogues nanocomposite for MRI-guided multimodal therapy for breast cancer - Min Zhang; Yanping Wu; Xingchen Lu; Yuhan Qin; Cong Zhang; Wenjie Gu; Ruochen Gao; Yuanyuan Qi; Meng Wang; Qingli Huang (Chemical Engineering Journal, 2024)

Quick measurement method of three components in lignocellulosic biomass based on kinetic mechanism analysis of PT-TGA - Gongxiang Song; Dexin Huang; Aishu Li; Ruochen Li; Song Hu; Kai Xu; Qiangqiang Ren; Hengda Han; Yi Wang; Sheng Su; Jun Xiang (Fuel, 2024)

Experimental study on impedance dispersion characteristics and electrical resistivity of high temperature granite - Biao Shu; Ruochen Huang; Jinqiang Tan; Diquan Li (Geothermics, 2024)

A comprehensive investigation of three long‐term precipitation datasets: Which performs better in the Yellow River basin? - Ruochen Huang; Bin Yong; Fan Huang; Hao Wu; Zhehui Shen; Da Qian (International Journal of Climatology, 2024)
The fifth generation European Centre for Medium‐Range Weather Forecasts Reanalysis on global land surface (ERA5‐Land), the Multi‐Source Weighted‐Ensemble Precipitation (MSWEP), and the Climate Hazards Group Infrared Precipitation with Stations (CHIRPS) are three representative precipitation estimates with quasi‐global coverage, high‐resolution and long‐term record. This study concentrates on investigating, for the first time, the long‐term spatiotemporal accuracy and regional applicability of these precipitation estimates at a daily scale in the Yellow River basin (YRB) using 39 complete years of data record (1981–2019), with a special focus on their capability on monitoring the extreme precipitation events with short duration and the continuous heavy precipitation events. Results indicate that MSWEP generally performs better than ERA5‐Land and CHIRPS in almost all seasons and subregions, with the highest Pearson correlation coefficient and critical success index, lowest root mean square error and false alarm ratio. ERA5‐Land presents a severe overestimation of precipitation amount, particularly in the plateau climate region (BIAS = 52.27%), but well reflects its spatial–temporal patterns in the YRB. As for the detecting capability, MSWEP shows the best accuracy in detecting extreme precipitation, particularly in maximum consecutive 5‐day precipitation (RX5day). The MSWEP better represents the spatial distribution of maximum 1‐day precipitation and maximum consecutive 5‐day precipitation in the YRB, but it shows a significant overestimation in zone Southern Qinghai. MSWEP and CHIRPS have better performance of temporal variation consistency in annual precipitation with ground reference than ERA5‐Land, while ERA5‐Land performs well in capturing extreme precipitation temporal variation, especially for continuous heavy precipitation events. This study can provide useful guidance when choosing long‐term precipitation products for hydrometeorological applications and climate‐related studies in the YRB.

Environmental economic profiles of expressway construction via life cycle assessment - Yimiao Huang; Xiaokuan Zhao; Ruochen Zhang; Panpan Xie; Guixiang Xue; Guowei Ma (Environmental Impact Assessment Review, 2024)

Efficiency of scientific and technological resource allocation in Chengdu–Chongqing–Mianyang Urban agglomeration: based on DEA–Malmquist index model - Ruochen Li; Yuyan Luo; Borui Chen; Huan Huang; Ping Liu (Environment, Development and Sustainability, 2023)

Study on Position and Shape Effect of the Wings on Motion of Underwater Gliders - Jiafeng Huang; Hyeung-Sik Choi; Mai The Vu; Dong-Wook Jung; Ki-Beom Choo; Hyun-Joon Cho; Phan Huy Nam Anh; Ruochen Zhang; Jung-Hyeun Park; Joon-Young Kim; Huy Ngoc Tran (Journal of Marine Science and Engineering, 2022)
A typical structure of an underwater glider (UG) includes a pair of fixed wings, and the hydrodynamic force driving the glider forward as descending or ascending in the water is generated primarily by the fixed wings. In this paper, a simplified glider motion model was established to analyze the dynamics in an easier way, and whose simulation results do not differ from the original one. Also, in the paper, the effects of the wing position and wing shape on the UG to the motion were studied. Since no direct analytic approach cannot be performed, the case study of the effects of six different wing positions and three wing shapes on gliding performances which are gliding speed, gliding angle and gliding path were performed through computer simulation. The simulation results revealed that when the fixed wing is located far from the buoyancy center to the tail end, more traveling range is achieved with less energy. Also, effect of the shape difference of the wings were analyzed. Shape changes did not show much difference on the travelling performance of the UG. In addition to these, the transient mode of the UG was studied. To control this, the PID controller for the position of the mass shifter and piston were applied. By application of the PID controller to the linearized dynamics equations, it was shown that the transient behavior of the UG was quickly and steadily controlled.

Octyl substituted butenolides from marine-derived Streptomyces koyangensis - Hongbo Huang; Yongxiang Song; Ruochen Zang; Xin Wang; Jianhua Ju (Natural Product Research, 2021)